Neutrophil extracellular traps in upper respiratory tract secretions: insights into infectious and allergic rhinitis - Zawrotniak, Marcin; Juszczak, Magdalena; Mosio-Wójcik, Justyna; Rapala-Kozik, Maria (Frontiers in Immunology, 2023)
Neutrophil extracellular traps (NETs) are structures released by neutrophils in response to various infections. NETs have a biocidal role and have been demonstrated to be effective against bacteria, fungi, viruses, and parasites. Depending on the situation, NETs can protect the host from pathogen invasion or contribute to the development of autoimmune diseases such as cystic fibrosis and rheumatoid arthritis. In this study, we aimed to investigate the occurrence of NET as one of the components in upper respiratory tract secretions in infectious and allergic diseases. Nasal mucus was collected from donors diagnosed with infectious rhinitis or allergic rhinitis. The extracellular DNA content was determined using SytoxGreen staining, and the total protein pool was determined using the microBCA method. Micrococcal nuclease was used to digest the samples and ELISA was employed to identify the NET proteins. The enzymatic activity of elastase was determined. Our findings showed that nasal mucus collected from patients with infectious rhinosinusitis contained extracellular DNA that could come from a variety of sources, responsible for increasing the density and viscosity of secretions, as well as NETs proteins. The identified enzymatic activity of NET elastase indicates the possible irritation of nasal tissues. However, the DNA content was not identified in the samples from allergic patients. In addition, we have shown in preliminary studies that therapy using N-acetylcysteine can liquefy nasal secretions.The study suggests that the composition of nasal mucus varies according to the cause of mucosal irritation. The presence of DNA and NET proteins can have severe consequences for the therapeutic process prolonging treatment. The low viscosity of nasal mucus in allergic patients facilitates mucosal flushing and the removal of allergens. Understanding the occurrence and role of NETs in various respiratory diseases is critical for developing effective treatment strategies that consider the complex interaction between the immune system and pathogens. The results of this study suggest that NETs may be present in upper respiratory tract secretions with an infectious background, supporting basic defense mechanisms using eosinophils and EETs. Further research is needed to explore the potential of NETs as a therapeutic target in respiratory diseases.